DARE Newsletter, Vol. 7, No. 1, Winter 2004 - DARE; Hall, Joan Houston; Simon, David (Dictionary of American Regional English, 2004)
Contents: "Bobbasheely" by Joan Houston Hall; "Funding Update" by David Simon; "Coming in Volume V"; "Notes and Quotes"; "Contributors to DARE in 2003"; "Volunteer Profile: Marjory McMickle"; "DARE on Capitol Hill"; "Where Are They Now?: Jason Sweet"
Quarterly newsletter of the Dictionary of American Regional English
Keywords: Americanisms; Dictionaries; Lexicography; Regional English; English Language--Dialects--United States